Strengthening and Retrofitting of Reinforced Concrete Hollow Columns using High Strength Ferrocement Fibers Composites - Mahmoud, Akram S.; Yaseen, Sinan A.; Shafeeq, Samar S. (Al-Nahrain Journal for Engineering Sciences, 2017)
Eight RC circular hollow columns (external diameter = 220 mm, internal diameter = 100 mm, length = 1000 mm and the hollow part = 700mm) casted and strengthened with ferrocement fibers composites to illustrate the behavior of these columns under concentric and eccentric axial compression force. Two columns where used as reference columns, which were repaired after failure to be tested as retrofitted columns. Six specimens were strengthened with one and two WWM layers as required. The variables considered included number of the WWM layers (N), the loading configuration and the eccentricity value (e) of loading. The ferrocement thickness was constant at 20 mm in all retrofitted and strengthened specimens.The test results revealed that the maximum increase in the ultimate concentric loads were 67% by strengthening the reference column with two layers of WWM, and the maximum increase in the ultimate eccentric load of columns was 78% by increasing of the WWM from one to two layers. For a constant number of WWM layers, the change from concentric to eccentric force caused a decrease in the ultimate load value attaining 73.5% for one- layer WWM strengthened columns. The failure of columns occurred by yielding of steel reinforcement followed by concrete crushing (i.e. tension failure).